The conceptual dimension of knowledge organization in the ISKO proceedings domain: A Bardinian content analysis - Guimarães, José Augusto Chaves [UNESP]; De Sales, Rodrigo; Martínez-Ávila, Daniel; Alencar, Maíra Fernandes (My University, 2014)
This paper aims to study the conceptual dimension of Knowledge Organization (KO) in the ISKO proceedings (1990-2012) domain. After analyzing a corpus of 71 papers that presented the term knowledge organization in their titles, using the methodology of Bardin's content analysis, it was possible to obtain a set of 11 definitions of KO which were studied using the following categories: nature, object, tools, processes, and perspectives/approaches. These categories act as a basis to identify the communities of authors that interact in the domain under different conceptual perspectives. The results show that KO has been mainly understood as an area or field of knowledge whose objects are recorded knowledge and conceptual structures, and whose main processes are classification and indexing, as well as information retrieval. The nature of KO is mostly linked to the construction of specialized discourses and the methodological dimension of such area is related to the systematization of recorded scientific knowledge.